Customer Perception on AI-Enabled 3D Graphics in E-commerce Platforms - Gowsiga, G; Rahini, S (International Journal of Engineering and Management Research, 2025)
The incorporation of AI-enabled 3D graphics is transforming the e-commerce sector by enhancing how customers experience products online. This study investigated customer perception of AI-driven 3D graphics on e-commerce platforms, focusing on their impact on engagement, satisfaction, and purchasing decisions. With features like virtual try-on and interactive 3D product views, e-commerce platforms are addressing traditional online shopping limitations, allowing customers to visualize products more accurately and make informed choices. This research explored how users perceive the benefits of these tools in terms of trust, ease of use, and product understanding. Through a survey- based approach, the study analyzes various factors influencing customer perception, such as the added value of 3D graphics, demographic influences, and previous digital experience. The findings aim to reveal how AI-driven 3D graphics can enhance customer engagement and reduce uncertainty, while also identifying potential limitations related to usability and realism. This paper seeks to provide insights into the role of AI-enabled 3D graphics in improving customer experience and driving higher conversion rates on e-commerce platforms. Recommendations are offered for businesses looking to optimize these tools to meet evolving customer expectations and enhance the digital shopping experience. The rapid advancement of Artificial Intelligence (AI) and 3D graphics technology has transformed the e-commerce landscape, enhancing customer experiences through immersive and interactive visual representations. This study aims to explore customer perceptions of AI-enabled 3D graphics in e-commerce platforms, focusing on their impact on purchasing decisions, engagement, and trust in online shopping. The research investigates key factors such as realism, interactivity, ease of use, and personalization to determine their influence on customer satisfaction. Through a combination of surveys and case studies, this study seeks to provide insights into consumer attitudes, expectations, and potential challenges associated with AI-powered 3D graphics.